Three-dimensional (3D) hepatic cell culture models to improve the clinical translation of nanobiomaterials (NBMs) - Tutty, Melissa Anne (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2021)
Despite the wide-reaching applications of nanoparticles that may be used for medical applications, i.e. nanobiomaterials or NBMs, in human health and medicine, their translation to the clinic is staggering slow, with a major issue being unintended liver accumulation and toxicity. In vitro 2D cell-based assays and in vivo testing are the most popular and widely used methods for assessing liver toxicity at preclinical stages; however, these methods have many limitations in assessing NBM hepatotoxicity. One potential way of overcoming this is by adopting more human-relevant models, such as in vitro 3D hepatic spheroids. These have shown great promise in detecting, in a predictive manner, the effects of various hepatotoxins in humans, thanks to their enhanced human-specific structure and functionality when compared to conventional 2D monocultures. The aim of this Ph.D. project is to assess whether hepatic mono- and multi-cellular 3D spheroids can be successfully applied to the pre-clinical assessment of nanobiomaterials (NBMs), i.e. nanoparticles with medical applications The working hypothesis is that, since 3D hepatic spheroid models are a better predictor of NBM safety than conventional 2D monocultures, this model could successfully bridge the gap between existing in vitro screening methodologies and in vivo animal models for assessing the toxicity effects of NBMs. Two NBMs are used for the proof-of-concept study: (i) LipImageTM815 and (ii) NR668 PEBCA, two dye-loaded NBMs with applications in drug delivery and deep tissue imaging. To date, these NBMs have never been tested in hepatic mono- and multi-cellular hepatic spheroids. 20nm gold nanoparticles (AuNPs) are also used as benchmark NBM, as their toxicity was previously assessed in HepG2 monoculture spheroids. 3D spheroids were formed in scaffold-free, non-adherent environments, and their liver-specific structure and function assessed using a variety of techniques, e.g., microscopy, histology, and ELISA. NBM characterisation was undertaken before 2D and 3D cultures were treated with each NBM and assessed using epifluoroscent and confocal microscopy to determine uptake profiles of NBMs in both culture types. Finally, quantitative in vitro safety assessment was assessed in 3D spheroids using a variety of commonly used assays for NBM pre-clinical assessment, i.e., cytotoxicity and genotoxicity. Results indicate that 3D hepatic mono- and multi-cellular spheroids display in vivo-like cellular morphology, secondary structure formation, expression of localised hepatic transporters, and enhanced liver-specific functions when compared to 2D cultures. Furthermore, NBMs accumulate in 3D spheroids in a pattern similar to what is observed in in vivo studies reported in the scientific literature. 2D cultures are more sensitive to the effects of NBMs, with 3D monoculture HepG2 spheroids exhibiting greater resistant, in a similar manner to what is observed in vivo. When incorporating an NPC cell line into the model (HepG2/LX-2 multicellular spheroid model), greater variation and less resistance to NBMs is observed. Overall, this work shows that hepatic spheroid models are promising advanced in vitro models for toxicity assessment of NBMs and may also help with bringing forward the 3Rs(Replacement, Reduction and Refinement) principle in animal research. Future work will include probing the expression of various enzymes involved in drug and NBM metabolism, i.e., cytochrome P450 (CYP450) enzymes, within the 3D hepatic spheroids developed. As mitochondrial dysfunction and damage has implications in up to 50% of hepatotoxins and many NBMs, it may be of interest to assess mitochondrial functionality in spheroids and apply this to toxicity screening of NBMs. A detailed study of how each NBM is internalized into spheroids, i.e., via active or passive transport, may also be on interest. As multicompartmental microfluidics devices are now commercially available for many sources, it would also be useful to extend the model into an organ-on-a-chip model.
APPROVED
Keywords: nanomedicine; cancer; nanobiomaterials; REFINE project; spheroids; 3Rs; 3D culture